2009
DOI: 10.1371/journal.pone.0004369
|View full text |Cite|
|
Sign up to set email alerts
|

ACC2 Is Expressed at High Levels Human White Adipose and Has an Isoform with a Novel N-Terminus

Abstract: Acetyl-CoA carboxylases ACC1 and ACC2 catalyze the carboxylation of acetyl-CoA to malonyl-CoA, regulating fatty-acid synthesis and oxidation, and are potential targets for treatment of metabolic syndrome. Expression of ACC1 in rodent lipogenic tissues and ACC2 in rodent oxidative tissues, coupled with the predicted localization of ACC2 to the mitochondrial membrane, have suggested separate functional roles for ACC1 in lipogenesis and ACC2 in fatty acid oxidation. We find, however, that human adipose tissue, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Primary antibodies (Lipin-1 (RD, AF3885), lipin-2 (Santa Cruz, sc-134433), ACACB (Cell signal Technology, 3662) [24], Malonyldecarboxylase (abcdm, ab95945) and β-Actin (Santa cruz, sc-81178)) were detected by appropriate HRP-conjugated secondary antibody followed by ECL detection.…”
Section: Methodsmentioning
confidence: 99%
“…Primary antibodies (Lipin-1 (RD, AF3885), lipin-2 (Santa Cruz, sc-134433), ACACB (Cell signal Technology, 3662) [24], Malonyldecarboxylase (abcdm, ab95945) and β-Actin (Santa cruz, sc-81178)) were detected by appropriate HRP-conjugated secondary antibody followed by ECL detection.…”
Section: Methodsmentioning
confidence: 99%
“…2e). Acetyl-CoA carboxylase (ACC) enhances fatty acid synthesis or lipogenesis (Castle et al 2009;Harada et al 2007), and phosphorylating this enzyme inhibits its function, reducing synthesis and enhancing the oxidation of fatty acids (Dasgupta and Milbrandt 2007;Harada et al 2007). We assessed the phosphorylation level of ACC and found that it signiWcantly increased with resveratrol treatment (Fig.…”
Section: Reduced Lipids and Enhanced Phosphorylation Of Acetylcoa Carmentioning
confidence: 99%
“…Much of the work on ACC to date has focused on animal studies, where cellular distribution of ACC and mRNA tissue expression patterns suggested separate functional roles for ACC1 and ACC2 ( 1,(6)(7)(8)(9). However, recent examination of human ACC expression indicates greater expression of ACC2 in both oxidative and lipogenic tissues ( 10 ).…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
“…Nevertheless, work by Pape et al demonstrated that starvation and diabetes reduced ACC mRNA as well as ACC activity (i.e., changes in the level of mRNA correspond to changes in the activity and amount of acetyl-CoA carboxylase), leading the authors to conclude that physiological conditions that affect fatty acid synthesis do so, in part, by modulating ACC gene expression ( 45 ). More recently Castle et al demonstrated that overexpression of ACC2 isoforms [the usual ACC2v.1 and a novel isoform (ACC2.v2)] increase ACC2 enzymatic activity to a similar extent, indicating that changes at the protein level translate to alterations in activity ( 10 ). It is also possible that this SNP may be a surrogate marker for other functional SNPs of ACC2 or other genes in the region.…”
Section: Replication Of Genetic Associations and Gene-nutrient Interamentioning
confidence: 99%